Volume 8: Mechanics of Solids, Structures and Fluids 2012
DOI: 10.1115/imece2012-87464
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Geometry Reconstruction Techniques for the Simulation of Non-Classical Aileron Buzz

Abstract: A computational study of non-classical aileron buzz is presented, which focuses on computational grid details for accurate simulations of this type of nonlinear transonic phenomenon. The analysis points out that mesh refinement is crucial to obtain reliable results and that the choice between a smoothed and non-smoothed geometry has an influence on the system response, both quantitatively and qualitatively. As a matter of fact, grid details affect the simulation of shock dynamics, which is the driving mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The reliability of the presented numerical model and problem setup has been extensively established by earlier research works (Romanelli et al 2010, Fusi et al 2012, Biganzoli and Quaranta 2009 through various tests and by tackling a set of realistic static and dynamic aeroelastic problems. A C-mesh with hexahedral elements is used to model the flow.…”
Section: Test and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reliability of the presented numerical model and problem setup has been extensively established by earlier research works (Romanelli et al 2010, Fusi et al 2012, Biganzoli and Quaranta 2009 through various tests and by tackling a set of realistic static and dynamic aeroelastic problems. A C-mesh with hexahedral elements is used to model the flow.…”
Section: Test and Resultsmentioning
confidence: 99%
“…It extends ±10 chords both chordwise and in the airfoil thickness direction. A convergence study reported in (Fusi et al 2012) showed that with about 50000 elements it is possible to reach a sufficient degree of spatial convergence.…”
Section: Test and Resultsmentioning
confidence: 99%
See 2 more Smart Citations